Carbon sources and trophic structure in a macrophyte‐dominated polyculture pond assessed by stable‐isotope analysis. (November 2016) - Mao, Zhi G.; Gu, Xiao H.; Zeng, Qing F.; Chen, Hui H.
Summary: Freshwater polyculture systems should efficiently utilise natural food resources and pond habitats with the consequent effects of reducing costs and increasing productivity. However, understanding of the primary carbon sources and food web within polyculture ponds, and especially macrophyte‐dominated ponds, remains limited. Stable‐isotope analysis was used to identify the main carbon sources and describe the trophic patterns of freshwater fauna in a polyculture pond around Lake Gucheng, China. An isotope mixing model (SIAR) was also used to estimate the relative contribution of four basal sources (suspended particulate organic matter [SPOM], sedimentary organic matter [SOM], macrophytes and epiphytes) to invertebrates and different fish trophic groups. Basal resources showed distinct δ 13 C values, ranging from −24.3 to −20.5‰, which allowed for a powerful discrimination of carbon sources. Consumers were also well separated in δ 13 C (−24.0 to −20.0‰ for invertebrates and −24.4 to −18.9‰ for fish), suggesting considerable differences in ultimate sources of carbon. Results from the SIAR model indicated that epiphytes were the most important carbon sources for crustaceans, herbivorous fish, omnivorous fish and piscivorous fish, while SPOM made the highest contribution to zooplankton, chironomids, molluscs, annelids, planktivorous fish and benthivorous fish. Mean δ 15 N values, combined with calculated food source contributions, were used to elucidate the food‐web structure of this polyculture pond, which suggested that carbon fixed by primary producers could be transported up the food chain to piscivorous fish through four main trophic pathways: one based mainly on SPOM, one on both SPOM and SOM, one on SPOM, SOM, macrophytes and epiphytes, and one based on both macrophytes and epiphytes. Our results emphasised the trophic importance of epiphytes on submerged macrophytes, a key component in the polyculture ponds, for the main culture species: Chinese mitten crab ( Eriocheir sinensis: Varunidae), freshwater shrimp ( Macrobrachium nipponense : Palaemonidae), and high‐value piscivorous fish. This study also revealed the high level of complexity of polyculture pond food webs, and suggests that a diversity of major trophic pathways may be a characteristic of macrophyte‐dominated aquatic ecosystems.